New distributional record of Rotala juniperina (Lythraceae) for Asia with typification of three names - R., Arun Prasanth; Sharma, Oshin A.; Sardesai, Milind M. (Phytotaxa, 2021)
Rotala juniperina, so far known only from East Africa, is reported here for the first time from peninsular India. The present paper encompasses a note on its taxonomy and distribution along with the designation of a lectotype for R. rotundifolia and epitypes for R. serpyllifolia and R. simpliciuscula.